MODEL OF FLEXIBLE-PERIODIC VEHICLE ROUTING PROBLEM SIMULTAN PICKUP AND DELIVERY - ALDERIZAL - Nim: 23414028 , MUHAMMAD
Transportation plays an important role in the supply chain system which also greatly affects the cost component. Suppressing transportation costs means reducing overall logistics costs. One of the problems that occur in transportation is to determine the route of the vehicle that can minimize the cost, the number of vehicles used, or known as the Vehicle Routing Problem (VRP). VRP with periodic visits is one of VRP variants. The problems raised in this study is to determine the route of the vehicle on pick-up and delivery process, flexibly-periodically, considering the time window, and vehicle capacity. The cost component to be considered is the cost of transportation consisting of the fixed cost of the vehicle, the variable cost of the vehicle and the inventory cost consisting of handling cost on the Retailer. This problem is usually encountered in the distribution of goods to franchised stores units. Flexible profits in shipping quantities are able to maximize vehicle capacity which ultimately reduces the use of vehicle quantities. This research develops a mathematical model of flexible-periodic vehicle routing problem on pick-up and delivery process. This research produces linear programming formulation of integers of three indices. The solution search process is performed using a branch-and-bound algorithm with Lingo 17.0 software.